1993
DOI: 10.1016/0035-9203(93)90095-8
|View full text |Cite
|
Sign up to set email alerts
|

Short course albendazole treatment for neurocysticercosis in Columbia

Abstract: The efficacy of albendazole was evaluated in 20 Colombian patients with neurocysticercosis showing neurological symptoms. All had parenchymal non-enhancing cystic images by computerized tomography and a positive enzyme-linked immunosorbent assay for cysticercus antibodies in serum or cerebrospinal fluid. They stayed in hospital for 8 d during treatment with albendazole, 15 mg/kg/d in 2 divided doses, and were then followed for at least 6 months after treatment. The number of cysts was reduced by 50% after 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…10,11 This trial showed that combined albendazole plus praziquantel—and increased albendazole (although to a less degree)—kills more cysts than does standard-dose albendazole. This increase in efficacy did not occur in patients with one to two cysts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 This trial showed that combined albendazole plus praziquantel—and increased albendazole (although to a less degree)—kills more cysts than does standard-dose albendazole. This increase in efficacy did not occur in patients with one to two cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Cyst damage is likely to lead to the release of parasite antigens and boost the immune response attack, in a process that involves an effect of praziquantel. We selected the combination of albendazole and praziquantel on the basis of their individual efficacy against cysticercosis, 611 different mechanisms of action, 12,13 findings from previous in-vitro and animal studies, 26,27 series of treatment of hydatid disease, 28 and findings from early studies in neurocysticercosis. 18,19 In our initial pharmacokinetics study, albendazole concentrations increased by roughly 50% in the combined treatment group, 14 thus we added an increased albendazole group to this trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the dose previously used in hydatid disease (15 mg/kg/day) was used for cysticercosis. The initial length of therapy was 1 month, later reduced to 15 days and 1 week (2,3,14,21,29,55,63,89,90,94,95,98,111). There is limited experience with higher doses of both drugs (1,11,58).…”
Section: Vol 15 2002 Guidelines For Treatment Of Neurocysticercosismentioning
confidence: 99%
“…12 However, ABZ only kills approximately 70% of cysts and clears all living parasites in only 30% to 40% of treated patients after a course of treatment. 7,13,14 On the basis of previous successful studies of pig treatment with oxfendazole (OFZ), this controlled study was developed to explore the efficacy of combined therapy (ABZ plus PZQ) versus ABZ or PZQ alone. Nitazoxanide (NZX), a broad-spectrum drug with activity against a wide variety of intestinal parasites in animals and humans 15,16 was also evaluated.…”
Section: Introductionmentioning
confidence: 99%